Non-Contact Electro Capacitive Cancer Therapy (ECCT) Modulate the mRNA Expression of PDGF and IL-1 in DMBA-induced Breast Cancer Rat - Hidayah, Nurul; Sakinah, Feby Nur; Annisa, Dyah Retno (International Journal of Cell and Biomedical Science, 2023)
Background: Breast cancer remains the most prevalent cancer among women globally, with significant mortality rates. Traditional therapies, such as surgery, chemotherapy, and radiotherapy, are associated with severe side effects and resistance, highlighting the need for alternative treatments. Electro-Capacitive Cancer Therapy (ECCT) is a promising non-invasive approach that uses low-intensity electric fields to selectively target cancer cells. Objective: This study aims to investigate the molecular mechanisms of ECCT, particularly its effects on key molecules such as PDGF and IL-1 in a DMBA-induced rat breast cancer model. Materials and Methods: The study used a post-test-only control group design with four groups: NINT (normal tissue), NIT (untreated tumor tissue), INT (DMBA-induced tumor tissue), and IT (ECCT-treated tumor tissue). ECCT was applied at 150 kHz for 21 days. mRNA expressions of PDGF and IL-1 were quantified using quantitative RT-PCR. Results: ECCT significantly reduced the mRNA expression of PDGF and IL-1 in treated tumor tissues (IT) compared to untreated tumor tissues (INT), bringing their levels closer to those observed in normal tissue (NINT). This suggests that ECCT downregulates key pro-angiogenic and pro-inflammatory molecules involved in tumor progression. Conclusion: In conclusion, the non-contact ECCT with a frequency of 150 kHz might downregulate PDGF and IL-1 mRNA expression in rat breast tumor tissue.